Kiegészítő adatok az erdélyi református népoktatás 18. századi történetéhez és Backamadarasi Kiss Gergely munkásságához - PÉTER, István (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2015)
Additional data to the History of the Reformed Education in the 18ᵗʰ Century and to the activity of Backamadarasi Kiss Gergely. Between old papers in an old house we find some old documents, what after the first reading seems to be part of an important act linked to the beginning of the public education in Transylvania. It contains three documents, which are mentioned by Kolumbán Vilmos and Sebestyén Kálmán in some studies and books, but none of them published in fact the documents. The first document is a letter of Backamadarasi Kiss Gergely sent to the Curators of the Principal Consistorium, Deans and Nobils from Transylvania. The second document contains instructions to the School Inspectors, who will be named by the Consistorium. The third document is about the rules of the School Teachers. Now we are publishing the hole documents which we found. Between old papers in an old house we find some old documents, what after the first reading seems to be part of an important act linked to the beginning of the public education in Transylvania. It contains three documents, which are mentioned by Kolumbán Vilmos and Sebestyén Kálmán in some studies and books, but none of them published in fact the documents. The first document is a letter of Backamadarasi Kiss Gergely sent to the Curators of the Principal Consistorium, Deans and Nobils from Transylvania. The second document contains instructions to the School Inspectors, who will be named by the Consistorium. The third document is about the rules of the School Teachers. Now we are publishing the hole documents which we found.